Grxcr1 regulates hair bundle morphogenesis and is required for normal mechanoelectrical transduction in mouse cochlear hair cells. - Beatriz Lorente-Cánovas; Stephanie Eckrich; Morag A Lewis; Stuart L Johnson; Walter Marcotti; Karen P Steel (PLoS ONE)
Tasmanian devil (tde) mice are deaf and exhibit circling behaviour. Sensory hair cells of mutants show disorganised hair bundles with abnormally thin stereocilia. The origin of this mutation is the insertion of a transgene which disrupts expression of the Grxcr1 (glutaredoxin cysteine rich 1) gene. We report here that Grxcr1 exons and transcript sequences are not affected by the transgene insertion in tde homozygous (tde/tde) mice. Furthermore, 5'RACE PCR experiments showed the presence of two different transcripts of the Grxcr1 gene, expressed in both tde/tde and in wild-type controls. However, quantitative analysis of Grxcr1 transcripts revealed a significantly decreased mRNA level in tde/tde mice. The key stereociliary proteins ESPN, MYO7A, EPS8 and PTPRQ were distributed in hair bundles of homozygous tde mutants in a similar pattern compared with control mice. We found that the abnormal morphology of the stereociliary bundle was associated with a reduction in the size and Ca2+-sensitivity of the mechanoelectrical transducer (MET) current. We propose that GRXCR1 is key for the normal growth of the stereociliary bundle prior to the onset of hearing, and in its absence hair cells are unable to mature into fully functional sensory receptors.